2008
DOI: 10.1080/10584580802541023
|View full text |Cite
|
Sign up to set email alerts
|

ENHANCED MAGNETIZATION IN BiFeO3/BaTiO3 MULTILAYERS: AN INTERFACE EFFECT?

Abstract: We have used pulsed laser deposition to grow BiFeO 3 /BaTiO 3 multilayers on SrTiO 3 substrates. The samples are characterized by Reflection High Energy Electron Diffraction (RHEED), Atomic Force Microscopy (AFM), and by X-ray diffraction measurements and modelling. The two multilayers investigated here have modulation periods A = 90Å and 180Å, while the total thickness of 1800Å is the same for both samples. Hence, twice as many interfaces are encountered for the A = 90Å than for the A = 180Å sample. SQUID mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This tendency remains for the samples grown at 0.01 mbar but with about 50% smaller saturation magnetization (not shown here). This result is in good agreement with the observations made by (Toupet et al 2008). Toupet showed that the magnetization in BTO/BFO multilayers increases when the number of interfaces in the superlattice increases.…”
Section: Multiferroic Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…This tendency remains for the samples grown at 0.01 mbar but with about 50% smaller saturation magnetization (not shown here). This result is in good agreement with the observations made by (Toupet et al 2008). Toupet showed that the magnetization in BTO/BFO multilayers increases when the number of interfaces in the superlattice increases.…”
Section: Multiferroic Propertiessupporting
confidence: 93%
“…Only a few BFO-containing composites have been investigated up to now: (a) strain-mediated composite nanostructures BFO with CoFe 2 O 4 (Zavaliche et al 2005, Dix et al 2009, Aimon et al 2012, NiFe 2 O 4 (Zhan et al 2006) or Fe 3 O 4 (Weal et al 2010); (b) exchange-mediated multiferroics with electric field control of exchange bias in BFO with FeCo (Chu et al 2008), Ni 78 Fe 22 or (LaSr)MnO 3 (Wu et al 2010) and (c) combinations of BFO with another ferroelectric phase such as BTO: BFO/BTO multilayers showed an increased magnetization with double number of interfaces in structures with identical total thickness (Toupet et al 2008). Substitution of BFO by (NdBi)FeO 3 and BTO by BaSrTiO 3 in the multilayers results in even higher magnetization, up to 60 emu cm −3 (Ivanov et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Some research groups have also studied BFO/BTO multilayered structures, but their photovoltaic properties are scarcely reported. 20,21 Toupet et al 22 and Yang et al…”
Section: Introductionmentioning
confidence: 99%
“…It may be seen from the recent research that the properties may be enhanced by material engineering including doping with other metal ions or making multilayered structures [11][12][13][14][15][16][17]. Touplet et al and Yang et al reported an enhancement in magnetic properties by employing BiFeO 3 /BaTiO 3 multilayer system [18][19]. Lorenz et al showed that BaTiO 3 -BiFeO 3 multilayers show the highest magnetization of 2.3 emu cm −3 , due to interface magnetic moments and exchange coupling [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the multilayered thin film structures, two different ferroic order materials allow modifications of the properties of parent materials by strain engineering [12]. BiFeO 3 /BaTiO 3 multilayers provide with a promising alternative in exploring the full potential of BiFeO 3 single layer thin film while maintaining the ferroelectric nature [18][19]. There have been few reports in recent years on improvement in multiferroic properties in multilayered thin film structures [12][13].…”
Section: Introductionmentioning
confidence: 99%